2016
DOI: 10.1016/j.jseaes.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

δ18O and δ13C records from a Cenozoic sedimentary sequence in the Lanzhou Basin, Northwestern China: Implications for palaeoenvironmental and palaeoecological changes

Abstract: In northwestern China, carbonate δ 18 O variation has been closely associated with evaporation and precipitation, whereas the variation of carbonate δ 13 C generally reflects patterns of palaeovegetation. Located within the transitional zone between the Chinese Loess Plateau and the Tibetan Plateau, the Lanzhou Basin has developed a continuous sequence of Cenozoic sediments which have been subjected to detailed sedimentological and high-resolution magnetostratigraphic analyses. In the present study, pedogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 104 publications
1
20
0
Order By: Relevance
“…2), which can be assigned to a distinct early Oligocene aridification in Central Asia, a feature confirmed by the δ 18 O data. This aridification step has to be differentiated from the well-known Eocene–Olicocene Transition aridification event at ~33 Ma (Meng and McKenna 1998; Dupont-Nivet et al 2007; Kraatz and Geisler 2010; Abels et al 2011; Wang et al 2012; Bosboom et al 2014; Caves et al 2014; Li et al 2016) as it post-dated it clearly. This shift at ~31 Ma correspond to the boundary between Biozone A and B.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…2), which can be assigned to a distinct early Oligocene aridification in Central Asia, a feature confirmed by the δ 18 O data. This aridification step has to be differentiated from the well-known Eocene–Olicocene Transition aridification event at ~33 Ma (Meng and McKenna 1998; Dupont-Nivet et al 2007; Kraatz and Geisler 2010; Abels et al 2011; Wang et al 2012; Bosboom et al 2014; Caves et al 2014; Li et al 2016) as it post-dated it clearly. This shift at ~31 Ma correspond to the boundary between Biozone A and B.…”
Section: Discussionmentioning
confidence: 92%
“…δ 18 O values of pedogenic carbonates are mainly determined by the δ 18 O composition of the soil water, which in turn is strongly related to the δ 18 O composition of local meteoric water, being affected by soil temperature and evaporation rate (Cerling 1984; Quade et al 1989; Li et al 2016). It has been shown that in semi-arid and arid areas, the ratio soil water evaporation/amount of precipitation has the most significant effect (Quade and Cerling 1995; Li et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations